Features of the clinical course and approaches to the therapy of norovirus infection in children - R. V. Popova; T. A. Ruzhentsova (Лечащий Врач, 2021)
The frequency, nature and duration of extra-intestinal manifestations depending on the therapy in children with norovirus infection were studied. It was found that in norovirus infection in children, in addition to gastrointestinal symptoms, there are often other symptoms that affect the upper respiratory tract, pancreas, hepatobiliary and urinary systems and heart. An effective drug that relieves the symptoms of norovirus infection, prevents the development of extra-intestinal manifestations and complications, is colloidal silicon dioxide.